HIV/AIDS IN PREGNANT WOMEN IN BRAZIL: 20-YEAR ANALYSIS - Gurgel Fernandes Távora, Lara (2024)
The incidence of HIV infection in women has increased in Brazil in the last two decades, leading to a greater attention to mother-to-child transmission (MTCT) and Aids in children < 5 years old data. Analyze the associa-tion of HIV/Aids incidence in women and pregnant women in Brazil, between 2000-2020, with MTCT rate. Ret-rospective study, based on HIV infection data collected from DATASUS, SICLOM, SISCEL, SIM and SINAN systems. HIV infection was more prevalent in fertile women, aged 20 to 39 years old. Even though a reduction of Aids cases in children < 5years old was observed, an increase of HIV infection in pregnant women was identified at the same time (p<0,001). These findings are probably associated with an improvement in prenatal care, with early treatment of pregnant women and virologic control, leading to a decrease in MTCT and Aids in children < 5years old.